The structure–activity relationship of various YO compounds, novel plasmin inhibitors, in the apoptosis induction - Enomoto, Riyo; Sugahara, Chiyoko; Komai, Tomoe; Suzuki, Chie; Kinoshita, Noriko; Hosoda, Akiko; Yoshikawa, Asa; Tsuda, Yuko; Okada, Yoshio; Lee, Eibai (Biochimica et biophysica acta, 2004)
We have previously reported that YO-2, a selective plasmin inhibitor, induces thymocyte apoptosis. To elucidate the mechanism of YO-2-induced apoptosis, other YO compounds with different plasmin inhibitory action were tested for the pro-apoptotic activity in this study. The treatment of rat thymocytes with the YO compounds which had the hydrophobic but not the hydrophilic moiety at the C-terminal increased DNA fragmentation, the number of condensed nuclei and caspase-3-like activity. All pro-apoptotic YO compounds not only were potent plasmin inhibitors but also had the hydrophobic C-terminal as the common structure. Therefore, the target molecule of the YO compounds may be located not on the cell surface but rather inside the cells.